LC/MS/MS of amino acid and peptide melphalan adducts. (8th February 2016) - Dewaele, Debbie; Sobott, Frank; Lemière, Filip
Abstract : Rationale: Melphalan is a frequently used chemotherapeutical agent for the treatment of myeloma, breast cancer, ovarian cancer and sarcoma of soft tissue. A good knowledge of the reactivity of the drug toward the different amino acids, e.g. covalent adduct formation, is crucial for the understanding of its activity and side effects during cancer treatment. Methods: The reactivity of melphalan and sites of adduct formation were studied by in vitro incubation of melphalan with free amino acids and glutathione as a model peptide. The formed covalent adducts were investigated using ultra‐performance liquid chromatography tandem mass spectrometry (UPLC/MS/MS) using a triple‐quadrupole instrument. Accurate mass measurements for the confirmation of characteristic product ions were performed on a quadrupole time‐of‐flight (QTOF) mass spectrometer. Results: The incubation of melphalan with different classes of amino acids resulted in the formation of adducts on the amino and carboxyl termini, as well as adduct formation in the reactive side chains of Cys, Met, Tyr, His, Lys, Asp and Glu. All these melphalan adducts could be identified by their characteristic collision‐induced dissociation (CID) product ion patterns. Conclusions: The present study demonstrates the reactivity of melphalan towards the functional groups of amino acids. The different alkylation site products show distinctive fragmentation patterns, which enable a fast identification of the different melphalan adducts. This study is a first important step towards a better understanding of the adduct formation in more complex molecules, e.g. peptides and proteins. Copyright © 2016 John Wiley & Sons, Ltd.